Posttranslational Modifications of Chloroplast Proteins: An Emerging Field. Issue 3 (24th April 2015) - Lehtimäki, Nina; Koskela, Minna M.; Mulo, Paula
Abstract : Chloroplast proteins are targets of numerous posttranslational modifications that allow precise regulation of chloroplast metabolism during environmental changes and challenges. Abstract: Posttranslational modifications of proteins are key effectors of enzyme activity, protein interactions, targeting, and turnover rate, but despite their importance, they are still poorly understood in plants. Although numerous reports have revealed the regulatory role of protein phosphorylation in photosynthesis, various other protein modifications have been identified in chloroplasts only recently. It is known that posttranslational N α -acetylation occurs in both nuclear- and plastid-encoded chloroplast proteins, but the physiological significance of this acetylation is not yet understood. Lysine acetylation affects the localization and activity of key metabolic enzymes, and it may work antagonistically or cooperatively with lysine methylation, which also occurs in chloroplasts. In addition, tyrosine nitration may help regulate the repair cycle of photosystem II, while N -glycosylation determines enzyme activity of chloroplastic carbonic anhydrase. This review summarizes the progress in the research field of posttranslational modifications of chloroplast proteins and points out the importance of these modifications in the regulation of chloroplast metabolism.